Determining consequences of retinal membrane guanylyl cyclase (RetGC1) deficiency in human Leber congenital amaurosis en route to therapy: residual cone-photoreceptor vision correlates with biochemical properties of the mutants - Samuel G. Jacobson; Artur V. Cideciyan; Igor V. Peshenko; Alexander Sumaroka; Elena V. Olshevskaya; Li-Hui Cao; Sharon Schwartz; Alejandro J. Román; Melani B. Olivares; Sam Sadigh; King‐Wai Yau; Elise Héon; et al. (2012)
The GUCY2D gene encodes retinal membrane guanylyl cyclase (RetGC1), a key component of the phototransduction machinery in photoreceptors. Mutations in GUCY2D cause Leber congenital amaurosis type 1 (LCA1), an autosomal recessive human retinal blinding disease. The effects of RetGC1 deficiency on human rod and cone photoreceptor structure and function are currently unknown. To move LCA1 closer to clinical trials, we characterized a cohort of patients (ages 6 months—37 years) with GUCY2D mutations. In vivo analyses of retinal architecture indicated intact rod photoreceptors in all patients but abnormalities in foveal cones. By functional phenotype, there were patients with and those without detectable cone vision. Rod vision could be retained and did not correlate with the extent of cone vision or age. In patients without cone vision, rod vision functioned unsaturated under bright ambient illumination. In vitro analyses of the mutant alleles showed that in addition to the major truncation of the essential catalytic domain in RetGC1, some missense mutations in LCA1 patients result in a severe loss of function by inactivating its catalytic activity and/or ability to interact with the activator proteins, GCAPs. The differences in rod sensitivities among patients were not explained by the biochemical properties of the mutants. However, the RetGC1 mutant alleles with remaining biochemical activity in vitro were associated with retained cone vision in vivo. We postulate a relationship between the level of RetGC1 activity and the degree of cone vision abnormality, and argue for cone function being the efficacy outcome in clinical trials of gene augmentation therapy in LCA1.